Access to interpreting services in England: secondary analysis of national data - Quirke Terry; Shankar Aparna; Gill Paramjit S; Freemantle Nick (BMC, 2009)
Abstract Background Overcoming language barriers to health care is a global challenge. There is great linguistic diversity in the major cities in the UK with more than 300 languages, excluding dialects, spoken by children in London alone. However, there is dearth of data on the number of non-English speakers for planning effective interpreting services. The aim was to estimate the number of people requiring language support amongst the minority ethnic communities in England. Methods Secondary analysis of national representative sample of subjects recruited to the Health Surveys for England 1999 and 2004. Results 298,432 individuals from the four main minority ethnic communities (Indian, Pakistani, Bangladeshi and Chinese) who may be unable to communicate effectively with a health professional. This represents 2,520,885 general practice consultations per year where interpreting services might be required. Conclusion Effective interpreting services are required to improve access and health outcomes of non-English speakers and thereby facilitate a reduction in health inequalities.